COVID-19 and Total Laryngectomy—A Report of Two Cases. (January 2021) - Paderno, Alberto; Fior, Milena; Berretti, Giulia; Del Bon, Francesca; Schreiber, Alberto; Grammatica, Alberto; Mattavelli, Davide; Deganello, Alberto
Objective: To date, no cases have been reported on the effects of COVID-19 in laryngectomees. Case Presentation: We herein presented two clinical cases of laryngectomized patients affected by COVID-19, detailing their clinical course and complications. Discussion: In our experience, permanent tracheostomy did not significantly affect the choice of treatment. However, dedicated devices and repeated tracheal toilettes may be needed to deal with oxygen-therapy-related tracheal crusting. Conclusion: In conclusion, laryngectomees should be considered a vulnerable population that may be at risk for worse outcomes of COVID-19 due to anatomical changes in their airways. The role of the ENT specialist is to guide airway management and inform the support-staff regarding specific needs of these patients.